Causes, Effects and Management of Infertility Among Reproductive Women in Karim Lamido Local Government Area of Taraba State-Nigeria (Texas Journal of Medical Science, 2023)
This study examined the causes, effects and management of infertility among reproductive women in Karim Lamido Local Government Area of Taraba State. Data were collected from the primary source using survey research design. A sample of 385 respondents was drawn and used to represent the entire population of the study. The research instrument was validated and tested using Alpha cronbach with the reliability coefficient of 0.84. Data collected were analyzed using descriptive statistics of frequency, simple percentage, mean and standard deviation. The results showed: endocrine defect, unsafe abortion, excessive use of illegal drugs and Obesity are the main causes of infertility. The study also found that shame and anxiety, psychological problem, divorce and stigmatization are the main effects of infertility among women of reproductive age. Recommendations: Public enlightenment programmes relating to an understanding of infertility, and access to relevant services should be developed as part of reproductive health education to include recognition of infertility (or sub-fertility) as a result of obesity, smoking, delayed childbirth (men and women), increased sexual activity/partners without use of barrier methods, early menopause due to family history, cancer before or during reproductive years, and other factors; infertility services covering a comprehensive range of fertility strategies should be complementary to population policies and programmes of maternal and child health